Mothers of sick babies dare not cause trouble: A commentary on Hassankani et al. (2020). Issue 4 (August 2021) - Harrison, Denise; Larocque, Catherine; Modanloo, Shokoufeh
Abstract: This letter to the editor reports on the article by Hassankhani et al. (2020), which reports on an ethnographic study of mothers' role during painful procedures in a neonatal intensive care unit (NICU). Participants were mothers (n = 18) and NICU nurses (n = 15) caring for medically stable newborns in a NICU in Iran. Much of what was reported goes against known and recommended best evidence of neonatal pain management, as well as the bigger picture of family-centred care (FCC) in the NICU.